Effects of Salinity Stress at Reproductive Growth Stage on Rice (Oryza sativa L.) Composition, Starch Structure, and Physicochemical Properties - Yao, Dongping; Wu, Jun; Luo, Qiuhong; Zhang, Dongmeng; Zhuang, Wen; Xiao, Gui; Deng, Qiyun; Bai, Bin (Frontiers in Nutrition, 2022)
The aim of the study was to investigate the changes of polished rice composition, starch structure and physicochemical properties from three rice cultivars treated by medium and high salinity stress at reproductive growth stage. The results showed that salt stress led to poor milling and appearance quality, higher total starch content, protein content, higher proportion of the medium and long chain of amylopectin as well as gelatinization temperature, but lower amylose content and lower proportion of the short chain of amylopectin. Compared with salt-sensitive cultivar, the salt-tolerant cultivars exhibited lower gelatinization temperature and gelatinization enthalpy, better pasting properties and more stable crystal structure, therefore their eating and cooking quality was less affected. The above results imply that salt stress at reproductive growth stage can degrade eating and cooking quality, and slightly increase pasting property of starch from salt-tolerant rice cultivar.